Antibacterial film product and preparation process
By using nano-grade activated carbon silver-loaded antibacterial agent and polycarbonate microsphere structure in antibacterial plastic films, the problems of the antibacterial effect of existing antibacterial plastic films are solved, and significant antibacterial effect and environmental protection are achieved.
Patent Information
- Application Number
- CN202510031851.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The existing antibacterial plastic films have shortcomings in the durability and environmental safety of antibacterial effects. Ultra-finement of antibacterial agents may cause harm to the human body and the environment, and the antibacterial effect is difficult to maintain for a long time.
Nano-grade activated carbon silver-loaded antibacterial agent is used, and the loading performance of the antibacterial agent is increased through the polycarbonate microsphere structure, so that it is evenly and stably dispersed in the matrix, avoiding the migration of antibacterial agents and achieving long-term antibacterial.
It significantly improves the durability of the antibacterial effect, avoids the potential harm of antibacterial agents to the human body and the environment, and simplifies process operations and reduces energy consumption and material processing temperature.
Smart Images

Figure BDA0005234382620000091 
Figure BDA0005234382620000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of plastic films, and more specifically, to an antibacterial film product and a preparation process thereof. Background Art
[0002] Plastic film is a film made of polyvinyl chloride, polyethylene, polypropylene, polystyrene and other resins, used for packaging and as a coating layer. Plastic packaging and plastic packaging products occupy an increasingly larger share in the market, especially composite plastic flexible packaging, which has been widely used in food, medicine, chemical and other fields, among which food packaging accounts for the largest proportion, such as beverage packaging, quick-frozen food packaging, steamed food packaging, fast food packaging, etc. These products have brought great convenience to people's lives; at present, with the development of science and technology and the continuous improvement of people's quality of life, people's health awareness is also constantly improving, and antibacterial plastic film products are also widely used.
[0003] The antibacterial plastic films commonly used in the prior art mostly use silver ion antibacterial agents. Generally, the silver ion antibacterial agent is applied on the surface of the film to form the antibacterial film. After the antibacterial agent solution is applied on the surface of the substrate film, it is bonded with the middle layer material. Although the process is simple, there are also many problems, such as ultra-fine antibacterial agent powder, which will cause harm to the human body and the environment, and the antibacterial agent will make the surface composition uneven after drying, which limits the antibacterial effect and makes it difficult to kill bacteria for a long time, thereby affecting the long-term antibacterial effect.
[0004] With the development of society, people pay more and more attention to health, and thus the requirements for the antibacterial and mildew-proof properties of plastic films are getting higher and higher. Existing plastic films are increasingly difficult to meet the requirements. To this end, we propose an antibacterial and mildew-proof plastic film for packaging and a preparation method thereof. Summary of the invention
[0005] The following is a summary of some aspects of the present invention, but is not intended to limit the present invention. When there is a discrepancy between the disclosure of this specification and the referenced document, the disclosure of this specification shall prevail.
[0006] In view of the shortcomings of traditional antibacterial plastic films, the present invention develops an antibacterial film product and a preparation process.
[0007] An antibacterial plastic film is prepared by extruding, granulating, casting and stretching raw materials including the following components; the antibacterial plastic film comprises, by weight: 37-40 parts of polyvinyl chloride, 32-45 parts of a toughening agent, 17-19 parts of polycarbonate microspheres, 0.3-0.5 parts of an antioxidant, 1-3 parts of a lubricant, 0.9-1.2 parts of a light stabilizer and 2-5 parts of an antibacterial agent.
[0008] Furthermore, the toughening agent is selected from one or more of styrene-butadiene thermoplastic elastomer, methyl methacrylate-butadiene-styrene terpolymer, acrylonitrile-butadiene-styrene copolymer, linear low-density polyethylene resin, and ethylene-vinyl acetate copolymer; preferably linear low-density polyethylene resin.
[0009] Furthermore, the antioxidant is selected from one or more of benzene antioxidant 1010, antioxidant 168, antioxidant 3113, and antioxidant 1330; antioxidant 168 is preferred.
[0010] Furthermore, the lubricant is selected from one or more of fluorine-containing polymer lubricants, silicone lubricants, fatty alcohol lubricants, fatty acid lubricants, fatty acid ester lubricants, stearic acid amide lubricants, fatty acid metal soap lubricants, alkanes and oxidized alkanes lubricants, and micro-nanoparticle lubricants; preferably fatty alcohol lubricants.
[0011] Furthermore, the fatty alcohol lubricant is selected from one or more of fatty alcohol, polyol, polyethylene glycol, polypropylene glycol, and polyvinyl alcohol; preferably polyethylene glycol.
[0012] Furthermore, the light stabilizer is selected from one or more of light stabilizer 1130, light stabilizer 622, and hindered amine light stabilizer HS-944; light stabilizer 622 is preferred.
[0013] Furthermore, the antibacterial agent is selected from nano-scale silver-loaded antibacterial agents.
[0014] Furthermore, the nano-scale silver-loaded antibacterial agent is one or more of nano-scale zirconium phosphate-loaded silver, zeolite-loaded silver, activated carbon-loaded silver, copper phosphate-loaded silver, calcium phosphate-loaded silver, silica gel-loaded silver, and hydroxyapatite-loaded silver antibacterial agent; preferably activated carbon-loaded silver.
[0015] Furthermore, the method for preparing polycarbonate microspheres comprises dissolving polycarbonate solid particles in chloroform, then mixing tetraethyl orthosilicate and polycarbonate to obtain solution A; mixing ammonia water and anhydrous methanol, heating to obtain solution B; mixing solution A and solution B, heating and stirring, cooling statically, and centrifugally drying to obtain polycarbonate microspheres.
[0016] An antibacterial plastic film is prepared by extruding, granulating, casting and stretching raw materials including the following components; the antibacterial plastic film comprises, by weight: 37-40 parts of polyvinyl chloride, 32-45 parts of linear low-density polyethylene resin, 17-19 parts of polycarbonate microspheres, 1680.3-0.5 parts of antioxidant, 1-3 parts of polyethylene glycol, 6220.9-1.2 parts of light stabilizer and 2-5 parts of activated carbon loaded with silver.
[0017] Furthermore, an antibacterial plastic film is prepared by extrusion granulation, casting and stretching of raw materials including the following components; the antibacterial plastic film comprises, by weight: 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon loaded with silver.
[0018] Another object of the present invention is to provide a process for preparing an antibacterial plastic film based on the prior art. The technical solution is as follows:
[0019] The raw materials are mixed uniformly according to the weight proportions, and the antibacterial plastic film is obtained after extrusion granulation, casting and stretching.
[0020] Furthermore, in the process for preparing an antibacterial plastic film described in the present invention, the extrusion temperature is 180-200°C; the processing temperature of the casting roller is 110-200°C; the stretching temperature is 100-200°C; and the preheating time is 20-40 minutes.
[0021] Furthermore, in the process for preparing an antibacterial plastic film described in the present invention, the extrusion temperature is 200° C.; the processing temperature of the casting roller is 120° C.; the stretching temperature is 120° C.; and the preheating time is 25 min.
[0022] Beneficial technical effects of the present invention
[0023] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0024] The present invention adopts nano-scale activated carbon silver-loaded antibacterial agent as the antibacterial agent. The nano-scale material is added to the surface of the film, and the specific surface area is large. The polycarbonate microsphere structure increases the loading performance of the antibacterial agent, so that the antibacterial agent is evenly and stably dispersed in the matrix, avoiding the migration of the antibacterial agent caused by other factors, and can achieve long-term antibacterial effect with more significant antibacterial effect without affecting the light transmittance of the film; effectively reduce the material processing temperature, reduce torque, improve work efficiency and reduce energy consumption at the same time, the process operation is simple, safe and environmentally friendly, and is suitable for large-scale industrial production. DETAILED DESCRIPTION
[0025] Unless otherwise indicated or there is an obvious conflict in the context, all technical and scientific terms used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the invention belongs. If there is a conflict, the definitions provided in the application shall prevail. When a trade name appears in this article, it is intended to refer to the corresponding commodity or its active ingredient. All patents, published patent applications and publications cited herein are incorporated herein by reference.
[0026] Example 1 Preparation of polycarbonate microspheres:
[0027] 0.2 g of polycarbonate solid particles were put into a 100 ml beaker, and then 8 g of chloroform was poured into the beaker to dissolve at room temperature. 0.1 g of tetraethyl orthosilicate was put into the polycarbonate solution to obtain solution A.
[0028] Pour 15 g of aqueous ammonia and 20 g of anhydrous methanol into another 100 ml beaker, mix, and heat to 30° C. to obtain solution B.
[0029] Solution A and solution B were mixed, stirred at 25°C for 15 hours, and cooled to obtain a white emulsion. The white emulsion was centrifuged using a high-speed centrifuge, and the white precipitate was washed with anhydrous methanol and then centrifuged again. After three times, the white solid was vacuum dried at 100°C for 12 hours, and then ground to obtain polycarbonate microspheres.
[0030] Embodiment 2:
[0031] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0032] Embodiment 3:
[0033] 37 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0034] Embodiment 4:
[0035] 40 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0036] Embodiment 5:
[0037] 38 parts of polyvinyl chloride, 32 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0038] Embodiment 6:
[0039] 38 parts of polyvinyl chloride, 45 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0040] Embodiment 7:
[0041] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 17 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0042] Embodiment 8:
[0043] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 19 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0044] Embodiment 9:
[0045] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.3 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0046] Embodiment 10:
[0047] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.5 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0048] Embodiment 11:
[0049] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 1 part of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0050] Embodiment 12:
[0051] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 3 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0052] Embodiment 13:
[0053] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6220.9 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0054] Embodiment 14:
[0055] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.2 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0056] Embodiment 15:
[0057] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 2 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0058] Embodiment 16:
[0059] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 5 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0060] Embodiment 17:
[0061] 35 parts of polyvinyl chloride, 30 parts of linear low-density polyethylene resin, 15 parts of polycarbonate microspheres, 1680.1 parts of antioxidant, 0.5 parts of polyethylene glycol, 6220.5 parts of light stabilizer, and 1 part of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0062] Embodiment 18:
[0063] 45 parts of polyvinyl chloride, 50 parts of linear low-density polyethylene resin, 22 parts of polycarbonate microspheres, 1681.0 parts of antioxidant, 5 parts of polyethylene glycol, 6221.8 parts of light stabilizer, and 10 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0064] Embodiment 19:
[0065] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 180°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 110°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 100°C and the preheating time was 20 minutes.
[0066] Embodiment 20:
[0067] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 200°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 200°C and the preheating time was 40 minutes.
[0068] Embodiment 21:
[0069] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 150°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 100°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 90°C and the preheating time was 10 minutes.
[0070] Embodiment 22:
[0071] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 220°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 220°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 220°C and the preheating time was 60 minutes.
[0072] Embodiment 23:
[0073] 38 parts of polyvinyl chloride, 40 parts of ethylene-vinyl acetate copolymer, 18 parts of polycarbonate microspheres, 1680.3 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0074] Embodiment 24:
[0075] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 31130.5 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0076] Embodiment 25:
[0077] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 1 part of polypropylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0078] Embodiment 26:
[0079] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 3 parts of polyethylene glycol, 11301.0 parts of light stabilizer, and 3 parts of activated carbon silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0080] Embodiment 27:
[0081] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.2 parts of light stabilizer, and 3 parts of calcium phosphate silver were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0082] Embodiment 28:
[0083] 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, and 6221.0 parts of light stabilizer were mixed. The temperature of the antibacterial agent was heated to 60°C during mixing, and the mixing time was 2 minutes. A twin-screw extruder was used for extrusion granulation at 200°C. During the extrusion of the material, the vacuum degree was 0.3MPa. The standard film material was prepared by a casting machine. The temperature of the casting machine was 120°C. After passing through a film stretching machine, a stretching test was carried out according to a preset stretching ratio. The stretching temperature was 120°C and the preheating time was 25 minutes.
[0084] Embodiment 29:
[0085] 1. Antimicrobial testing standards and operating procedures:
[0086] Antibacterial test standards: GB / T 31402-2015 Test method for antibacterial performance of plastic surfaces, JC939 Antibacterial performance of antibacterial plastic pipes for construction, test bacteria: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538.
[0087] 2. The antibacterial test steps are tested in accordance with the antibacterial plastic testing standard GB / T 31402-2015. The specific steps are as follows: Disinfect the sample to be tested with 75% ethanol and dry it, and dilute the bacteria with sterile water to a bacterial suspension of appropriate concentration for use. Take 0.2mL of the bacterial suspension and drop it on the surface of the sample, cover it with a 0.1mm thick polyethylene film (4.0cm×4.0cm) to form a uniform liquid film between the sample and the film. Incubate at 37°C with a relative humidity of 90% for 18 to 24 hours. Wash the bacterial solution with sterile water, dilute it into an appropriate concentration gradient, and take 0.1mL and evenly spread it on the prepared sterile agar medium. Incubate at 37°C for 18 to 24 hours and observe the results. The negative control is replaced by a sterile plate, and other operations are the same; the antibacterial rate is calculated by the JC939-2017 method;
[0088] 3. Test of antibacterial durability: Soak the sample in 50℃ distilled water for 16 hours (boil), and then test it according to GB / T 31402-2015 standard.
[0089] Table 1 Test results of antibacterial thermoplastics
[0090]
[0091]
[0092] The above are the test results of the antibacterial properties of the antibacterial films prepared in Examples 1-27. The data show that the antibacterial films prepared in the present invention have better antibacterial properties.
[0093] The above is a description of a specific embodiment of the present invention. It should be understood that the present invention is not limited to the above embodiment, and the above embodiment and description are only for illustrating the principle of the present invention.
[0094] Those skilled in the art may make various non-substantial changes and improvements to the present invention without departing from the concept of the present invention, all of which fall within the scope of protection claimed by the present invention.
Claims
1. An antibacterial plastic film, prepared by extrusion granulation, casting and stretching of raw materials including the following components; the antibacterial plastic film comprises, by weight: 37-40 parts of polyvinyl chloride, 32-45 parts of toughening agent, 17-19 parts of polycarbonate microspheres, 0.3-0.5 parts of antioxidant, 1-3 parts of lubricant, 0.9-1.2 parts of light stabilizer, and 2-5 parts of antibacterial agent.
2. The antibacterial plastic film according to claim 1, characterized in that: The toughening agent is selected from one or more of styrene-butadiene thermoplastic elastomer, methyl methacrylate-butadiene-styrene terpolymer, acrylonitrile-butadiene-styrene copolymer, linear low-density polyethylene resin, and ethylene-vinyl acetate copolymer.
3. The antibacterial plastic film according to claim 1, characterized in that: The antioxidant is selected from one or more of benzene antioxidant 1010, antioxidant 168, antioxidant 3113, and antioxidant 1330.
4. The antibacterial plastic film according to claim 1, characterized in that: The lubricant is selected from one or more of fluorine-containing polymer lubricants, silicone lubricants, fatty alcohol lubricants, fatty acid lubricants, fatty acid ester lubricants, stearic acid amide lubricants, fatty acid metal soap lubricants, alkanes and oxidized alkanes lubricants, and micro-nanoparticle lubricants.
5. The antibacterial plastic film according to claim 1, characterized in that: The light stabilizer is selected from one or more of light stabilizer 1130, light stabilizer 622, and hindered amine light stabilizer HS-944.
6. The antibacterial plastic film according to claim 1, characterized in that: The antibacterial agent is selected from one or more of nano-scale zirconium phosphate silver-loaded, zeolite silver-loaded, activated carbon silver-loaded, copper phosphate silver-loaded, calcium phosphate silver-loaded, silica gel silver-loaded, and hydroxyapatite silver-loaded antibacterial agents.
7. The antibacterial plastic film according to claim 1, characterized in that: The preparation method of polycarbonate microspheres comprises the following steps: dissolving polycarbonate solid particles in chloroform, then mixing tetraethyl orthosilicate and polycarbonate to obtain solution A; mixing ammonia water and anhydrous methanol, and heating to obtain solution B; mixing solution A and solution B, heating and stirring, cooling statically, and centrifugally drying to obtain polycarbonate microspheres.
8. The antibacterial plastic film according to claim 1, characterized in that: It is prepared by extrusion granulation, casting and stretching of raw materials including the following components; The antibacterial plastic film comprises, by weight: 37-40 parts of polyvinyl chloride, 32-45 parts of linear low-density polyethylene resin, 17-19 parts of polycarbonate microspheres, 1680.3-0.5 parts of antioxidant, 1-3 parts of polyethylene glycol, 6220.9-1.2 parts of light stabilizer, and 2-5 parts of activated carbon-supported silver.
9. The antibacterial plastic film according to claim 1, characterized in that: It is prepared by extrusion granulation, casting and stretching of raw materials including the following components; The antibacterial plastic film comprises, by weight: 38 parts of polyvinyl chloride, 40 parts of linear low-density polyethylene resin, 18 parts of polycarbonate microspheres, 1680.4 parts of antioxidant, 2 parts of polyethylene glycol, 6221.0 parts of light stabilizer, and 3 parts of activated carbon-supported silver.
10. A process for preparing an antibacterial plastic film, wherein the extrusion temperature is 180-200°C; the processing temperature of the casting roll is 110- 200℃; stretching temperature is 100~200℃; preheating time is 20~40min.